2016
DOI: 10.1002/2016je005094
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of impact crater populations and the geochronology of planetary surfaces in the inner solar system

Abstract: Analyzing the density of impact craters on planetary surfaces is the only known technique for learning their ages remotely. As a result, crater statistics have been widely analyzed on the terrestrial planets, since the timing and rates of activity are critical to understanding geologic process and history. On the Moon, the samples obtained by the Apollo and Luna missions provide critical calibration points for cratering chronology. On Mercury, Venus, and Mars, there are no similarly firm anchors for cratering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 206 publications
(309 reference statements)
1
81
1
Order By: Relevance
“…The interpretation of the model ages therefore may not be straightforward and may represent a steady state between production and removal of craters (Öpik , ), or a diminishing sequence of resurfacing processes, thereby providing a retention age regulated by the destruction rate instead of a surface formation age (Chapman and Jones ; Smith et al. ; Michael ; Fassett ; Kite and Mayer ).…”
Section: Crater Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The interpretation of the model ages therefore may not be straightforward and may represent a steady state between production and removal of craters (Öpik , ), or a diminishing sequence of resurfacing processes, thereby providing a retention age regulated by the destruction rate instead of a surface formation age (Chapman and Jones ; Smith et al. ; Michael ; Fassett ; Kite and Mayer ).…”
Section: Crater Modificationmentioning
confidence: 99%
“…Established approaches to dating planetary surfaces through the analysis of a superposed crater population rely on the technique of binning the measured crater diameters, and attempting to use the thus divided data to resolve the characteristic shape and density of the accumulating crater population (Hartmann ; Crater Analysis Techniques Working Group ; Neukum ). The method has seen numerous fruitful applications (see listing of predictive successes in recent review by Fassett ), but has always required caution when the number of observed craters is low.…”
Section: Statistical and Observational Biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The crater count‐derived crater retention ages for the channels vary from ~0.2 to ~0.5 Ga [ Ivanov , ] (Figure b). It is important to mention here that the ages obtained for the channels do not straightaway represent the exact time of the fluvial activity, whereas they reflect the crater retention age over the channels [ Fassett , ] or plausibly lava flow resurfacing activity, which is evident from Figure a. The inferred ages are the lower limit for channels, as it is possible that high erosional activity could have altered the surface and the true age can be much older [ Fassett , ].…”
Section: Description and Analysismentioning
confidence: 99%
“…This technique has been greatly improved with new advances in sample analyses methods, cratering mechanics, orbital dynamics, and multiwavelengths high-resolution datasets obtained by recent lunar and deep space explorations. A review on the establishment, usage and new advances of this technique is detailed by Fassett (2016). It is not overstated that this technique has built most of the time frames a b d c Fig.…”
Section: Introductionmentioning
confidence: 99%